The impact of an educational forum intervention on East African mothers' HPV vaccine-related knowledge, attitudes, and intentions to vaccinate their adolescent children. Issue 28 (23rd June 2021) - Chu, Huong; Ko, Linda K.; Ibrahim, Anisa; Bille Mohamed, Farah; Lin, John; Shankar, Megha; Amsalu, Fanaye; Ali, Ahmed A.; Richardson, Barbra A.; Taylor, Victoria M.; Winer, Rachel L.
Highlights: An HPV vaccine education intervention targeted East African immigrant mothers. Education was delivered via small group forums by co-ethnic healthcare providers. Education increased mothers' knowledge and attitudes about HPV vaccines. Most said they were likely to vaccinate their adolescent children post-intervention. HPV vaccination in mothers' adolescent children was low over 6-month follow-up. Abstract: Objective: HPV vaccine uptake in U.S. East African adolescents is low. We developed and evaluated a culturally-targeted interactive educational intervention for East African immigrant mothers to increase HPV-vaccine-related knowledge, attitudes, and intentions to vaccinate adolescent children. Methods: Eligible mothers had ≥ 1 11–17-year-old child and reported all children's HPV vaccination status as unvaccinated or unknown. The intervention was delivered via 10 dinners in the Seattle metropolitan area (8 with the Somali community, 2 with the Ethiopian community). Educational presentations and pre/post-tests on knowledge, attitudes, and intentions were conducted in the participants' native language by a co-ethnic physician. Pre/post differences in responses were evaluated with McNemar's tests and GEE models. HPV vaccination uptake 6-months post-intervention was evaluated using state immunization registry data. Results: Of 115 participating mothers, most (84%) were Somali and < 40 years of age (60%). Median years of formal education was 8 (range 0–16), and 61% reported a household income <25, 000. Knowledge of HPV/HPV-vaccines was low pre-intervention, with correct responses ranging from 4% to 39% (61%-91% of responses were "not sure"); correct post-intervention responses ranged from 29% to 97%. Pre-intervention, only 12% of mothers thought they had enough information to make a decision about vaccination, compared to 90% post-intervention. Pre-intervention, only 16% of mothers reported that they were somewhat or very likely to vaccinate their child, compared to 83% post-intervention. All pre/post comparisons were statistically significantly different (p < 0.0001). Although mothers were more likely to report correct HPV-related knowledge and positive vaccine attitudes and intentions post-intervention, only two mothers' children initiated HPV vaccination within 6 months after the intervention. Conclusions: Results illustrate that a culturally targeted educational intervention effectively increased East African mothers' HPV vaccine-related knowledge, attitudes, and intentions to vaccinate their adolescent children. Future research should identify additional intervention components that can bridge the gap between intention and behavior to facilitate HPV vaccine uptake.